NONSTICK COVERINGS OF BELORUSSIAN PRODUCTION FOR IMPROVEMENT OF CASTINGS OF IRON-CARBON ALLOYS - D. M. Kukuj; Ju A. Nikolajchik; S. L. Rovin; N. V. Romanova (Литьë и металлургия, 2010)
The results of using of antipenetration coatings of Belorussian production for improvement of the castings quality of iron-carbon alloys are given.